Use of a Collagen I Matrix to Enhance the Potential of Circulating Angiogenic Cells (CACs) for Therapy - Ostojic, Aleksandra (Université d'Ottawa / University of Ottawa, 2015)
Acute myocardial infarction (MI) is the end result of many cardiovascular diseases and is one of the leading causes of death in the western world. Cell therapy, using circulating angiogenic cells (CACs) or CD34+ cells from peripheral blood, is one approach under investigation for restoring blood flow and function to the ischemic heart. However, the numbers of CACs and CD34+ circulating cells are inversely proportional to the severity of cardiovascular disease and age; therefore, there is a need to increase their numbers and/or function for therapy. One possibility is to enhance the therapeutic potential of the cells with the use of a biomaterial. In this study, we used a collagen matrix to culture human CD34+ circulating cells, and evaluated the effect of the matrix on CD34+ cell properties and function. The matrix was able to successfully increase proliferation, migration, CD34+ phenotype and branching in an angiogenesis assay. These functional benefits may be associated with the sonic hedgehog (Shh) pathway. The collagen matrix was previously shown to enhance the function of healthy CACs, but its ability to do the same for CACs from coronary artery disease patients is unknown. In this study, the matrix was shown to enhance the viability, proliferation and angiogenic potential of patient CACs. Furthermore, gene expression for integrins and Shh pathway components in the sub-population of CD34+ cells was similar between patient and healthy donors when isolated from CACs. This work provides insight into the mechanisms for the observed matrix-enhanced function of therapeutic CACs and CD34+ cells from both healthy and CAD patient donors.
Keywords: Biomaterials; CD34+ cells; Cell therapy; Cardiovascular disease; Integrins